Design and Efficiency Studies on Skimmers in an Active Grease Trap - Juffrizal, K.; Nidzamuddin, M.Y.; Tan, C.F.; Zulfattah, Z.M.; Shaifuddin, M.S.M.; Aizat, R.A. (Journal of Engineering and Technology (JET), 2014)
The objectives are to study the nature of fat, oil and grease and the correlation of retention time in separating these elements from wastewater. In addition, the assessment of the skimmers in term of the best material and shape in order to shorten the retention time. There are three types of grease traps which are passive, active and bio-remediation and the focus of this study is merely on the active grease trap. There will be three types of material will be tested for the skimmer, which are polyethylene foam, high- temperature nylon and clay. An active grease trap with a combination of three type materials for the skimmer were fabricated and experiments were conducted. From the collected data, the third skimmer (clay) has proven to be the best skimmer with 97.7% of oil were collected while the lowest is 70% which produced by the high-temperature nylon. In addition, clay has shown better consistency in collecting oil based on the three experiments with three different amounts of oil. From the obtained data, it can also be concluded that another factor that crucially affecting the result is in the grooves which were fabricated for the clay skimmer.